iB Dhuha Saving Product Analysis with Wadiah Contract at Bank Riau Kepri Bengkalis Branch - Revita Sari; Nur Azlina; Mistari Br Harianja; Norpatiha Norpatiha; Khotimatul Anisa; Zulfikar Hasan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The goal of this study is to figure out how to make the first deposit of Hajj iB savings. Dhuha with the system for implementing a wadiah contract on iB hajj savings and a wadiah contract. Dhuha at the Bengkalis Branch of Bank Riau Kepri. The qualitative research method was used to examine the Hajj iB savings product. Dhuha at the Bengkalis Branch of Bank Riau Kepri. This kind of research is field research that uses methods like interviews and documentation to collect data; Customers of the iB Dhuha hajj savings product at the Bank Riau Kepri Bengkalis Branch served as the study's subjects. Initial deposit funds for potential iB Dhuha savings customers at the Bank Riau Kepri Bengkalis Branch were the subject of this study. The Bank Riau Kepri Bengkalis Branch is the population, the Bank Riau Kepri Bengkalis Branch's customer service is the sample, and a structured interview guideline is the measurement scale used in this study. Descriptive qualitative analysis was used in data analysis. The study's conclusions were as follows: in the initial deposit made by customers of iB Hajj savings. Dhuha customers make an initial deposit of at least Rp at the Bank Riau Kepri Bengkalis Branch. 50,000,000, and the customer is free to make additional deposits of a minimum of Rp depending on their ability. up to Rp. 20,000, - 25,000,000.